A planar ultraviolet objective lens for optical axis free imaging nanolithography by employing optical negative refraction. Issue 8 (22nd March 2022) - Kong, Weijie; Liu, Ling; Wang, Changtao; Pu, Mingbo; Gao, Ping; Liu, Kaipeng; Luo, Yunfei; Jin, Qijian; Zhao, Chengwei; Luo, Xiangang
Abstract : Optical axis free imaging nanolithography could be achieved using a planar ultraviolet objective lens composed of a hyperbolic metamaterial. Abstract : Lithography is one of the most key technologies for integrated circuit (IC) manufacturing and micro/nano-functional device fabrication, while the imaging objective lens plays one important role. Due to the curved surface of the conventional objective lens, the imaging field of view is limited and the objective lens system is complex. In this paper, a planar objective lens based on the optical negative refraction principle is demonstrated for achieving optical axis free and long depth of focus imaging nanolithography. Through employing a hyperbolic metamaterial composed of silver/titanium dioxide multilayers, plasmonic waveguide modes could be generated in multilayers, which results in optical negative refraction and then flat imaging at ultraviolet wavelength. The corresponding imaging characteristics are investigated in simulation and experiment. At the I-line wavelength of 365 nm, the highest imaging resolution of 165 nm could be realized in the 100 nm photoresist layer under the working gap of 100 nm between the objective lens and substrate. Moreover, this planar objective lens has good ability for cross-scale and two-dimensional imaging lithography, and is similar to a conventional projection objective lens. It is believed that this kind of planar objective lens will provide a promising avenue for low-cost nanofabrication scenarios in the near future.